Sustainable Housing - Almusaed, Amjad, editor 650221; Almssad, Asaad, editor 650222 (London : Intechopen, 2022)
Sustainable housing is generally used to describe housing that is environmentally friendly and resource-efficient over the lifetime of the building. Homes are designed to have the least possible negative impact on the environment. This means energy efficiency, avoiding environmental toxins, and responsibly using materials and resources while having positive physical and psychological effects on inhabitants. This book presents a comprehensive overview of sustainable housing, starting from legislation and ending with the design and configuration of homes.